STUDI HABITAT DAN SUMBER PAKAN LEBAH KELULUT DI KAWASAN CAGAR ALAM GUNUNG NYIUT DESA PISAK KABUPATEN BENGKAYANG - Sanjaya, Vihenky; Astiani, Dwi; Sisillia, Lolyta (Universitas Tanjungpura, 2019)
Kelulut Bees is a stingless bee that produces honey, in the area of Gunung Nyiut Nature Reserve Kelulut Bees lives naturally with nests on tree trunks. It is not yet known how the habitat and sources of feed so that it is necessary to do research on the study of habitat and feed sources of Kelulut Bees. This study aims to obtain information about the condition of habitat and feed sources of Kelulut Bees. The method used was a survey with double plots which purposively placed, then identified the condition of habitat and feed sources. Types of hornet bees found were: Heterotrigona itama, Tetragonula laeviceps, Geniotrigona thoracica, Trigona carbonaria and Trigona drescheri. The bees nesting place were in living trees is (52%), dead trees (20%) and soil (28%). Daily mean temperature, air humidity and light intensity were 28.81 °C, 83.06%, and 583.76%. Soil type is PMK with pH 4.4, soil temperature 26.6 C °, soil moisture 26%. Altitude ± 360 masl. Tree analysis was dominated by Xanthophyllum amoenum 36.38%, Lepisanthes tetraphylla 38.01%, Syzgium chloranthum 45.8%, and Bellucia pentamera seedlings 51.58%. The feed sources at the observation sites were dominated by the family Myrtaceae and Dipterocarpaceae, while outside the plots the feed source was dominated by Cocos nucifera L, Durio zibethinus, Nephelium lappaceum L, Syzygium aqueum.Keywords : Feed source, Gunung Nyiut, habitat, kelulut bees, Nature Reserve.